2022
DOI: 10.2196/30989
|View full text |Cite|
|
Sign up to set email alerts
|

Improving Pelvic Floor Muscle Training Adherence Among Pregnant Women: Validation Study

Abstract: Background Mobile health apps, for example, the Tät, have been shown to be potentially effective in improving pelvic floor muscle training (PFMT) among women, but they have not yet been studied among pregnant women. Adherence to daily PFMT will improve pelvic floor muscle strength leading to urinary incontinence (UI) improvement during the pregnancy. Objective This study aims to document the validation process in developing the Kegel Exercise Pregnancy … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 53 publications
(66 reference statements)
0
3
0
Order By: Relevance
“…The results of our study regarding the practices of pregnant women performing PFMEs are inconsistent with the study, which highlighted that pregnant women had good knowledge, and half of those women were practicing PFMEs [7]. Another study reported similar results by recruiting 720 women during pregnancy and postpartum; approximately half of the pregnant women were performing these exercises during pregnancy, and most intended to perform them during the postpartum period [32].…”
Section: Discussioncontrasting
confidence: 86%
See 1 more Smart Citation
“…The results of our study regarding the practices of pregnant women performing PFMEs are inconsistent with the study, which highlighted that pregnant women had good knowledge, and half of those women were practicing PFMEs [7]. Another study reported similar results by recruiting 720 women during pregnancy and postpartum; approximately half of the pregnant women were performing these exercises during pregnancy, and most intended to perform them during the postpartum period [32].…”
Section: Discussioncontrasting
confidence: 86%
“…Pelvic floor disorders include urinary incontinence (UI) and dyspareunia, which may lead to temporary or permanent effects [5]. Enuresis is the other name for UI, defined as unpremeditated urine discharge, which is prevalent among 57.7% of females in low-and middle-income countries [6,7]. It affects women's health and quality of life by restricting physical activities and eliciting employment-related issues, emotional disturbance, behavioral problems, travel limitations, sleep disorders, and hindered prayers [8].…”
Section: Introductionmentioning
confidence: 99%
“…Fig 5 shows the utilization frequency of the strategies from the PSD model from Table 5 . On average, 6.3 persuasive features were used in the publications utilizing the PSD model listed in Table 5 , with 14 being the highest number of utilizations within 1 application [ 32 ], and 3 being the lowest [ 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, participant age details fluctuated among studies: while some omitted age specifics, others employed age brackets. For context, average participant ages were as follows: 31.6 years in Fenicio and Calvary’s study [ 48 ], 55.5 years in that by Mohadis and colleagues [ 32 ], 45.5 years in Renfrew and colleagues’ study [ 44 ], and 29.84 years in the work of Jaffar and colleagues [ 33 ]. The evaluation of each study hinged on 2 primary criteria: the outcome—categorized as mixed, positive, or negative—and the inherent risk of bias.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, there were no regulatory bodies for Tai Ji, and patients are in the dark about their therapist's capabilities in delivering and educating them on the proper effective Tai Ji move for stroke rehabilitation. Future studies could be conducted to validate Tai Ji with the incorporation within the mobile health development and evaluation framework for better usability and acceptability in stroke rehabilitation ( 76 ).…”
Section: Discussionmentioning
confidence: 99%